Chicken egg yolk antibodies (IgY)-based antivenom for neutralization of snake venoms: a review. (3rd July 2022) - Choraria, Ankit; Somasundaram, Rajeswari; Janani, S.; Rajendran, Selvakumar; Oukkache, Naoual; Michael, A.
Abstract: Snakebite and its envenomation are a significant health and economic burden worldwide. Animal (horse/sheep)-based immunoglobulins derived from hyperimmune animal serum or plasma is the current treatment modality for snake envenomation. Chicken egg yolk (IgY) antibodies in the recent past have become one of the promising tools for research as an alternative to these mammalian antibodies. IgY have been a reason of debate from past three decades for its applications in snakebite therapy. The ease of producing pure, specific, and high affinity antivenoms have shown that IgY antivenoms can be used for treating snake bites.